Milk: the new sports drink? A Review - Roy Brian D (Taylor & Francis Group, 2008)
Abstract There has been growing interest in the potential use of bovine milk as an exercise beverage, especially during recovery from resistance training and endurance sports. Based on the limited research, milk appears to be an effective post-resistance exercise beverage that results in favourable acute alterations in protein metabolism. Milk consumption acutely increases muscle protein synthesis, leading to an improved net muscle protein balance. Furthermore, when post-exercise milk consumption is combined with resistance training (12 weeks minimum), greater increases in muscle hypertrophy and lean mass have been observed. Although research with milk is limited, there is some evidence to suggest that milk may be an effective post-exercise beverage for endurance activities. Low-fat milk has been shown to be as effective, if not more effective, than commercially available sports drinks as a rehydration beverage. Milk represents a more nutrient dense beverage choice for individuals who partake in strength and endurance activities, compared to traditional sports drinks. Bovine low-fat fluid milk is a safe and effective post exercise beverage for most individuals, except for those who are lactose intolerant. Further research is warranted to better delineate the possible applications and efficacy of bovine milk in the field of sports nutrition.